2022
DOI: 10.3390/toxins14020145
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Individual and Combined Effects of T-2 Toxin, HT-2 Toxin and Neosolaniol on the Apoptosis of Porcine Leydig Cells

Abstract: T-2 toxin usually co-occurs with HT-2 toxin and neosolaniol (NEO) in the grains and feed. Our previous studies found that T-2 toxin and its metabolites’ binary or ternary combination exposure to porcine Leydig cells (LCs) displayed synergism in certain range of dosage and cannot be predicted based on individual toxicity. However, the possible mechanism of these mycotoxins’ combined exposure to cell lesions remains unknown. Based on 50% cell viability, the mechanism of apoptosis in porcine Leydig cells was inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…In vitro, PK15 cells were treated with a combination of AFB1 and T-2 to evaluate their toxicity and oxidative stress responses. The findings of this study revealed that AFB1 and T-2, alone or in combination, produced time-and dosage-dependent increasingly toxic effects on PK15 cells, which is similar to the effects of T-2 toxin and its metabolites observed on porcine Leydig cells [28]. Our initial findings revealed that, at equivalent doses, cell viability in the T-2 group was significantly lower than in the AFB1 group (Figure 1A,B), indicating that T-2 had a more pronounced effect on cell viability at the same concentration.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In vitro, PK15 cells were treated with a combination of AFB1 and T-2 to evaluate their toxicity and oxidative stress responses. The findings of this study revealed that AFB1 and T-2, alone or in combination, produced time-and dosage-dependent increasingly toxic effects on PK15 cells, which is similar to the effects of T-2 toxin and its metabolites observed on porcine Leydig cells [28]. Our initial findings revealed that, at equivalent doses, cell viability in the T-2 group was significantly lower than in the AFB1 group (Figure 1A,B), indicating that T-2 had a more pronounced effect on cell viability at the same concentration.…”
Section: Discussionsupporting
confidence: 72%
“…In Vero kidney cells, AFB1 and OTA not only showed an additive cytotoxic effect but also synergism to promote genotoxicity with increased DNA fragmentation [ 31 ]. There experiments indicate that the binary and ternary combinations of T-2, HT-2, and NEO displayed synergistic toxicity in porcine Leydig cells [ 28 ]. However, it should be noted that differences in cell model, toxin concentration, and incubation time may affect the effects of toxin combinations.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there may be antagonistic, additive, and synergistic effects among mycotoxins. For instance, the combination of AFB 1 and OTA can enhance its toxicity ( McKean et al, 2006 ; Xu et al, 2022 ). The combination of AFB 1 and T-2 increases their toxicity ( Hou et al, 2018 ; Xiao et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different indicators present different combined effects, resulting in reproductive toxicity (Alahmar, 2019). When exposed to the two toxins for 3 and 5 days, the mouse brain experiences a significant induction of oxidative stress and apoptosis, synergistically enhancing brain damage (Xu et al., 2022). However, urine metabolomics analysis has revealed an antagonistic toxic effect on the metabolism of mice when DON (2 mg/kg) and ZEA (20 mg/kg) are combined (Shi et al., 2018).…”
Section: Combined Toxicities Of Mycotoxinmentioning
confidence: 99%
“…Several physiological mechanisms are in place to maintain homeostasis. Factors such as infection, exposure to various compounds, including AFB1, and physical or thermal tissue injuries can trigger a complex early systemic reaction known as the APR (Xu et al., 2022). The APR plays a crucial role in ensuring survival during the immediate aftermath of an injury.…”
Section: Diagnostic Biomarker Of Acute Phase Proteins During Mycotoxi...mentioning
confidence: 99%